PENGETAHUAN EKOLOGI LOKAL - Eni Murdiati (Fakultas Dakwah dan Komunikasi, Universitas Islam Negeri, Raden Fatah Palembang, 2015)
The existence of local wisdom in the era of globalization is a phenomenon that continues to run, along with human life and culture. Utilizing continuous development of natural resources in order to improve the welfare and quality of life of the people. Limited availability of natural resources and uneven, both in number and in quality, while the demand for natural resources is increasing as a result of increased development activities to meet the needs of the increasing population and diverse. The development impact resulted in the carrying capacity of the environment can be disturbed and the environmental carrying capacity can be decreased. Given this reality, the local knowledge of local communities is also challenged by the need to meet the basic needs of an increasingly large and lifestyle faced by society.